New Insights into Applied Linguistics: Rethinking the Teaching of Tenses - Chouit, Drissia (Nusantara Science and Technology Proceedings, 2021)
This feature article presents a new approach to the teaching of grammar in universities: A Meta-operational Grammar of English. Tackling one of the most important chapters of English grammar, the teaching of tenses, it aims to show (1) the importance of teaching grammar in context; (2) the importance of investing linguistic research in this pedagogical process; and most importantly, (3) the prerogative of understanding how a language works to master it. In other words, when students know how language works, they learn it easily and effectively, and they master the use of grammatical forms in context. It is the teaching pedagogy that is at stake here: a pedagogy that addresses students’ intelligence and cognitive capacities to motivate them and help them become autonomous learners and skilled communicators.